Stem cell function is conserved during short-term storage of cultured epidermal cell sheets at 12°C - Ringstad, Håkon; Reppe, Sjur; Schøyen, Tine Hiorth; Tønseth, Kim Alexander; Utheim, Tor Paaske; Jackson, Catherine Joan (PLOS ONE, 2020)
Transplantation of cultured epidermal cell sheets (CES) can be life-saving for patients with large area burns. CES have also been successfully used to regenerate eye and urethral epithelia in animal models. Short-term storage aims to extend the transplantation window, offers flexibility in timing surgery and allows testing of CES quality, phenotype and sterility. This study investigated extended CES storage and explored the effect of additional re-incubation recovery time following storage. The proliferative quality of stored confluent versus pre-confluent CES was also investigated using functional testing. CES were stored at 12°C and results compared to non-stored control CES. Investigation of timepoints during 15 days storage revealed that viability began to deteriorate by day 11 and was associated with increased lactate in the storage medium. The percentage of apoptotic cells also significantly increased by day 11. Flow cytometry analysis of integrin β1 expression and cell size indicated best retention of stem cells at 7 days of storage. Functional testing of pre-confluent and confluent cells following 7 days storage showed that pre-confluent cells responded well to 1-day re-incubation after storage; they became highly prolific, increasing in number by 67%. Conversely, proliferation in stored confluent cells declined by 50% with 1-day re-incubation. Pre-confluent stored CES also had far superior stem cell colony forming efficiency (CFE) performance compared to the confluent group. Re-incubation improved CFE in both groups, but the pre-confluent group again out-performed the confluent group with significantly more colonies. In conclusion, a maximum storage period of 7 days is recommended. Use of pre-confluent cells and one day recovery incubation greatly improves viability, colony-forming ability and proliferation of cells stored for 7 days at 12°C. Thus, these recommendations should be considered under culture and storage of high-quality CES for clinical use.